1982
DOI: 10.1111/j.1365-2125.1982.tb01996.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of systemic prednisolone on arachidonic acid, and prostaglandin E2 and F2 alpha levels in human cutaneous inflammation.

Abstract: 1 In order to test the proposal that the anti-inflammatory effect of corticosteroids is attributable to inhibition of release of the prostaglandin precursor, arachidonic acid, the effect of systemic prednisolone on arachidonic acid and prostaglandin levels in abdominal skin of six patients receiving this treatment for alopecia totalis, was studied. 2 Inflammation was produced in an area of abdominal skin by topical application of 5% w/w tetrahydrofurfuryl nicotinate (THFN) cream. 3 The erythema produced was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…28 In addition, it represses the COX pathway, which generates inflammatory prostaglandins. 29 It is highly likely that the effect of prednisolone on AIH-mediated plasticity resulted from diminished NF-κB-mediated inflammation as described above, either within the CNS or periphery, thereby decreasing circulating pro-inflammatory molecules. 30 Increased circulating levels of the anti-inflammatory cytokine, IL-10, following prednisolone administration are consistent with the anti-inflammatory actions of prednisolone.…”
Section: Discussionmentioning
confidence: 97%
“…28 In addition, it represses the COX pathway, which generates inflammatory prostaglandins. 29 It is highly likely that the effect of prednisolone on AIH-mediated plasticity resulted from diminished NF-κB-mediated inflammation as described above, either within the CNS or periphery, thereby decreasing circulating pro-inflammatory molecules. 30 Increased circulating levels of the anti-inflammatory cytokine, IL-10, following prednisolone administration are consistent with the anti-inflammatory actions of prednisolone.…”
Section: Discussionmentioning
confidence: 97%
“…Another form of immunosuppressants- glucocorticoids which act by blocking the biosynthesis of PGE2 [ 130 ] might interfere with MSC functionality as MSCs support synthesis of PGE2 which in return is responsible for inhibiting T cell proliferation [ 131 ]. A report on lung resident MSCs derived from human lung allograft patients demonstrated that both COX2 selective and non-selective COX inhibitor drugs block the immunosuppressive potential of MSCs on host immune cells [ 132 ].…”
Section: Microenvironmental Cues Influencing Therapeutic Efficacy Of mentioning
confidence: 99%
“…Quanto ao AA, precursor dos compos- no plasma ou no TA de pacientes com infecção grave/crítica por SARS-CoV-2 que haviam sido tratados com glicocorticoides. Uma possível explicação seria quanto a origem do AA, o qual além de poder ser liberado por PLA2 ativada com cálcio [282], também pode ser liberado via fosfolipase insensível aos glicocorticoides [283], ou ainda ser advindo da destruição de adipócitos [284], do metabolismo do ácido linoleico [285], ou da degradação de endocanabinóides pela ácido graxo amida hidrolase (FAAH) [286], uma enzima detectada em pacientes infectados pelo SARS-CoV-2 [287]. Embora os glicocorticoides estejam sendo amplamente utilizados para reduzir as taxas de morbidade e mortalidade de pacientes com COVID-19, nem sempre os mesmos têm se mostrado amplamente eficazes [288], indicando que mais estudos precisam ser realizados.…”
Section: Resultados | 99unclassified